Microarray and qPCR Analyses of Wallerian Degeneration in Rat Sciatic Nerves - Yi, Sheng (Front Cell Neurosci, 2017)
Wallerian degeneration occurs immediately following injury to mammal peripheral nerves. To better understand the molecular events occurring during Wallerian degeneration, a rat model of sciatic nerve transection was used to assess differentially expressed genes at 0.5, 1, 6, 12, 24 h, 4 days, 1, 2, 3, and 4 weeks post nerve injury (PNI). Hierarchical clustering, Euclidean distance matrix, and principal component analysis (PCA) collectively suggested three distinct phases within the post-injury period of 4 weeks. Gene ontology (GO) analysis suggested that phase I (0–6 h PNI), phase II (6–24 h PNI), and phase III (4 days to 4 weeks) were associated with acute response to injury, preformation of Wallerian degeneration, and complete execution of Wallerian degeneration, respectively. Critical signaling pathways and transcriptional factor networks responsible for the regulation of Wallerian degeneration were further identified and integrated using Kyoto Enrichment of Genes and Genomes (KEGG) pathway analysis and Ingenuity Pathway Analysis (IPA), respectively. Our results may help to elucidate some molecular mechanisms of gene regulation associated with Wallerian degeneration that occurs after traumatic injury to peripheral nerve axons in mammals.